2014
DOI: 10.1371/journal.pone.0101038
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular Connective Tissue Differences in Spastic and Control Muscle: A Mechanical and Histological Study

Abstract: Cerebral palsy (CP) of the spastic type is a neurological disorder characterized by a velocity-dependent increase in tonic stretch reflexes with exaggerated tendon jerks. Secondary to the spasticity, muscle adaptation is presumed to contribute to limitations in the passive range of joint motion. However, the mechanisms underlying these limitations are unknown. Using biopsies, we compared mechanical as well as histological properties of flexor carpi ulnaris muscle (FCU) from CP patients (n = 29) and healthy con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
78
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(86 citation statements)
references
References 59 publications
6
78
0
2
Order By: Relevance
“…This agrees with the observation of Smith et al (2011). However, de Bruin et al (2014) suggest that the remainder of sarcomeres remain at lower lengths. Finite element modeling has shown that such distribution in sarcomere strain along fascicles is plausible theoretically Yucesoy, 2016, Turkoglu et al, 2014;Yucesoy and Huijing, 2012;Yucesoy et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This agrees with the observation of Smith et al (2011). However, de Bruin et al (2014) suggest that the remainder of sarcomeres remain at lower lengths. Finite element modeling has shown that such distribution in sarcomere strain along fascicles is plausible theoretically Yucesoy, 2016, Turkoglu et al, 2014;Yucesoy and Huijing, 2012;Yucesoy et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
“…In a recent study de Bruin et al (2014) compared mechanical as well as histological properties of flexor carpi ulnaris muscle (FCU) using biopsies from CP patients and healthy controls. They showed that tertiary perimysial structures inside the muscle, which are continuations of branches of the main neurovascular tracts, are thickened in spastic FCU.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Collagen that accumulates in the spastic muscle endomysium is thick and fibrotic, especially in severe cases, which suggests that collagen may increase the muscle stiffness in spasticity (2). De Bruin et al questioned the belief that the endomysium is affected in CP muscle (PLOS one 2014) instead highlighting the role of thickening of the tertiary perimysium (4). A study conducted in children with spastic diplegia noted a predominance of type 1 fiber in their spastic muscles (5).…”
Section: Introductionmentioning
confidence: 99%